Layanan Shopee Pinjam Perspektif Fatwa DSN MUI No. 117 Tahun 2018 - Puji Saputra, Bagus Setya; Abdul Hakim, Muhammad Haris (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Fatwa DSN-MUI No. 117 of 2018 provides guidelines for financial services based on information technology that must comply with Sharia principles. This fatwa emphasizes that such services must be free from prohibited elements, including riba (interest), gharar (uncertainty), maysir (gambling), tadlis (fraud), dharar (harm), and zhulm (injustice). Additionally, financial services are required to uphold principles of fairness, transparency, and balance in various contracts, such as sales contracts (al-bai'), profit-sharing systems (mudharabah and musyarakah), and benevolent loans (qardh). An analysis of Fatwa DSN-MUI No. 117 of 2018 regarding information technology-based financial services reveals that Shopee Pinjam still exhibits several aspects that are not fully aligned with Sharia principles. One major issue identified is the presence of riba in its repayment mechanism, as well as potential injustice in financing agreements that tend to disadvantage users. The fatwa asserts that all technology-based services must adhere to Sharia principles, including fairness, transparency, and balance, which Shopee Pinjam has not yet fully implemented. This research highlights the importance of applying contracts that align with Sharia principles and utilizing supportive infrastructure to ensure that fintech services comply with Islamic norms.